Literasi Keuangan dan Faktor Sosiodemografi terhadap Keputusan Investasi melalui Bias Perilaku - Farahiyah Sartika; Nurul Humairo (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
This study examines the effect of financial literacy and sociodemographic factors on stock investment decisions through behavioral bias as a variable intervention. By using purposive sampling technique, so that the number of research samples obtained was 109 members of investment galleries at State Islamic University Maulana Malik Ibrahim Malang, Brawijaya University, and State University of Malang. The results showed that financial literacy affects stock investment decisions and behavioral bias, while sociodemographic factors do not affect them. Behavioral bias influences stock investment decisions and it can mediate the effect of financial literacy on stock investment decisions but it is unable to mediate sociodemographic factors towards stock members' investment decisions in State Islamic University Maulana Malik Ibrahim Malang, Brawijaya University, and State University of Malang.